Analisis daya Saing Pariwisata Provinsi Sulawesi Tengah - Ira Nuriya Santi; Muzakir Muzakir; Rahmat Mubaraq; Muhammad Faisal; Benyamin Parubak (Universitas Batanghari, 2022)
This study aims to analyze the competitiveness of tourism in Central Sulawesi Province by using 5 (five) aspects of competitiveness, namely tourist objects and attractions; marketing aspects; aspects of transportation, telecommunications and information; accommodation and restaurant aspects; and souvenir aspects. Tourist perceptions of these five aspects will be the substance of the research. Descriptive research method using qualitative sampling technique is random sampling by distributing questionnaires to 100 tourists which is then carried out descriptive statistical analysis. The results of the analysis found that the competitiveness of tourism in Central Sulawesi Province only excels in the aspect of tourist objects and attractions, so it can be said that the competitiveness of tourism in Central Sulawesi Province is low.